Liquid hydrogen storage tank virtual crashworthiness design exploration for civil aircraft - Gallois, A.; Giannopoulos, Ioannis K.; Theotokoglou, Efstathios E. (IOP Publishing, 2023)
Civil aviation industry is researching for alternative fuel energy sources to substitute current hydrocarbon-based aviation fuels. Carbon free emissions flights could be achieved with fuels like Hydrogen either through combustion or via electricity producing fuel cells. It is of great importance to explore the airframe designs to house Hydrogen in its cryogenic liquified state. The objective of the study herein was to provide a conceptual qualitative analysis related to the crashworthiness behaviour of civil aircraft carrying liquid Hydrogen fuel storage tanks. The design parameters of interest were the storage tank location in the airframe, the structural energy absorption following crash landing scenarios and the structural deformation of the structure surrounding the tanks, penetrating the survival space of the occupants. Several structural design arrangements were proposed and compared. Simulation results indicated that the optimal location for the fuel storage greatly depends on the actual aircraft layout as well as on the future civil aircraft airworthiness requirements that are still under development for that type of fuel energy source.